Do planejamento à execução: uma contribuição para a cooperativa de agricultores familiares de Terra Alta - COSTA JÚNIOR, Rosalvo Alves (2018)
It is notable that the historical evolution of the administration as an area of knowledge demonstrates an ideological bias directly related to the development of the economic dimension, with strong epistemological influence of the positivist and functionalist sciences, that restricted its field of action to the maximization of profit; and, consequently, has created a gap in approaches needed to strengthen social organizations. Especially those based on selfmanagement and other economic principles of solidarity. Thus, in order to evaluate how the process of re-signification, adaptation and appropriation of a management tool could contribute to minimize the administrative difficulties faced by a popular cooperative, the present work aimed to develop the application of the PDCA Cycle in the scope of selfmanagement, through a participatory methodological process based on action research. In this perspective, based on a theoretical framework that seeks to discuss in a gradual and immersive way the use of the PDCA Cycle as a tool that can be redefined and appropriated by solidary economic projects aimed at strengthening family agriculture; and, at the same time, contribute to the broadening of the debate around the performance of the Administration itself; he went on to field research. In turn, by choosing the Farmers Cooperative of Terra Alta as an object of study, the work was divided into four stages that were characteristic of the adopted methodology, which, intertwined with the development phases of the PDCA Cycle, gradually contributed to the construction of a situational diagnosis and a process of integration and sharing of experiences and knowledge that culminated in the construction of a participatory process appropriate to the development of a structure of planning and execution of an action plan aimed at solving a problem chosen by the cooperative members themselves. Finally, we come to the idea that the use of the PDCA Cycle as an alternative to improve the management of self-managed enterprises, and to broaden the approach and performance of the Administration as a knowledge area is a viable alternative; provided that the procedure of resignification and appropriation of this instrument is preceded by a participatory and cautious involvement aimed at developing a process of learning and sharing of knowledge capable of strengthening economic principles of solidarity and valuing the intrinsic organizational culture in the organizational sphere.